An Application of the Khumbelo Function on the Camellia Algorithm to Prevent Attacks in IoT Devices - Khumbelo Difference Muthavhine; Mbuyu Sumbwanyambe (IEEE Access, 2023)
Camellia is an encryption algorithm implemented in many Internet of Things (IoT) devices. However, intruders attack the Camellia cipher using Substitution Box (S-Box) distinguishers. The distinguishers are tables that provide probabilities for guessing the secret keys of the algorithms. Distinguishers are used in the majority of attacks. The most well-known distinguishers are Linear Approximation Table (LAT), Difference-Distribution Table (DDT), and Differential-Linear Connectivity Table (DLCT). This research focuses on preventing these attacks using a novel function called the Khumbelo function to distract the construction of S-Box distinguishers. The Khumbelo function distracted the distinguishers’ constructions by reducing the probability of building the table. The Khumbelo function successfully decreased the attack probability of LAT (from 54.6875 percent to 0 percent), DDT (from 1.5625 percent to 0 percent), and DLCT (from 50.0000 percent to 0 percent). The Khumbelo function is generated using a 4-Byte output S-Box instead of the original 1-Byte output S-Box in Camellia.